ANALISIS KANDUNGAN LOGAM BERAT Pb, Cu DAN Zn PADA DAGING DAN CANGKANG KERANG KEPAH (Meretrix meretrix) DI PERAIRAN BATUBARA SUMATERA UTARA - Doni Gunawan Tampubolon; Bintal Amin; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was carried out in April 2013 to analyze the content of heavy metal Pb, Cu and Zn in soft tissues and shells of hard clam (Meretrix meretrix) from coastal waters of Batubara and to find out the correlation between size and content of heavy metals in both hard and soft tissues, as well as to determine the safe level for consumption of this organism. The results showed that the content of heavy metals Pb in the shells is higher than in soft tissues while Cu and Zn is higher in the soft tissues. The average heavy metals content in soft tissues were different with size, where Pb (1,83 μg/g) and Cu (4,25 μg/g) was found to be higher in larger size and Zn (23,44 μg/g) was found to be higher in smaller size. In the shells Pb was higher in smaller size (2,96 μg/g), Cu was higher in larger size (4,35 μg/g) and Zn was higher in larger size (23,44 μg/g).